2016
DOI: 10.1007/jhep11(2016)179
|View full text |Cite
|
Sign up to set email alerts
|

There and back again: a T-brane’s tale

Abstract: T-branes are supersymmetric configurations described by multiple Dp-branes with worldvolume flux and non-commuting vacuum expectation values for two of the worldvolume scalars. When these values are much larger than the string scale this description breaks down. We show that in this regime the correct description of T-branes is in terms of a single Dp-brane, whose worldvolume curvature encodes the T-brane data. We present the tale of the journey to reach this picture, which takes us through T-dualities and rug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…In F-theory, these homomorphisms arise as "T-brane" data for two intersecting stacks of seven-branes probing a C 2 /Z N singularity (for a partial list of references to the T-brane literature, see references [37,39,44,91,107,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131]). In particular, we can turn on T-brane data for either stack of seven-branes, resulting in a theory labeled by a pair of homomorphisms ρ 1 , ρ 2 ∈ Hom(su(2), g).…”
Section: B U (1)'s From Group Theorymentioning
confidence: 99%
“…In F-theory, these homomorphisms arise as "T-brane" data for two intersecting stacks of seven-branes probing a C 2 /Z N singularity (for a partial list of references to the T-brane literature, see references [37,39,44,91,107,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131]). In particular, we can turn on T-brane data for either stack of seven-branes, resulting in a theory labeled by a pair of homomorphisms ρ 1 , ρ 2 ∈ Hom(su(2), g).…”
Section: B U (1)'s From Group Theorymentioning
confidence: 99%
“…In previous work [17], three of the authors and Minasian have shown that certain T-brane solutions preserving eight supercharges have a new description in the regime of parameters where the non-Abelian fields have large expectation values in string units, in terms of a collection of ordinary branes with commuting worldvolume scalars. This suggests a type of brane-brane duality, similar in spirit to the Myers effect [33,34], by which non-Abelian brane configurations in one regime of parameters correspond to charges and dipole moments of higher-dimensional Abelian branes in another regime of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for the brane-brane duality conjectured in [17] came via a rather indirect chain of reasoning that involved T-duality and the Myers effect, and depended crucially on certain details of the starting non-Abelian solutions. It is the purpose of this paper to show that this duality is a universal feature of all T-brane solutions, and to establish a way to systematically obtain the Abelian description of T-branes starting from their traditional non-Abelian description.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations